HIRARKI RUANG CANDI KEDATON MUARA JAMBI - Parama Putri, Kirana Anindita (UI Scholars Hub, 2026)
Kedaton Temple is one of the temples located in the Muara Jambi Temple Complex. Kedaton Temple, like most other temples in this temple complex, is composed of several rooms. Kedaton Temple in the Muara Jambi Temple Complex is considered the largest temple there. In addition, Kedaton Temple is composed of 14 rooms. The large number of rooms raises the question of how the existing spatial hierarchy is seen from the concept of Buddhist Cosmology. This research was conducted by conducting a literature study and analyzed using spatial analysis. The literature study was carried out by collecting sources such as books, journals, theses, and other written works related to the research material. The approach used is an archaeological and architectural approach. The archaeological approach is used to provide an interpretation of the temple building that will be linked to Buddhist cosmology, while the architectural approach is carried out by analyzing the spaces that make up Kedaton Temple. The results obtained are the hierarchy of Kedaton Temple is composed of three parts, namely the core courtyard, the middle courtyard, and the outer courtyard. The inner courtyard can be considered a sacred space, the middle courtyard is a semi-sacred space, and the outer courtyard is a profane space.